High-thermal-conductivity and low-thermal-resistance epoxy heat-conducting adhesive applied to high-power LED (light-emitting diode) heat dissipation component and preparation method
By using high-thermal conductivity and low thermal resistance epoxy thermal adhesive in high-power LED heat dissipation components, combined with low-viscosity epoxy resin, phase-change epoxy resin and modified low-melting metal powder, the problems of insufficient thermal conductivity and high thermal resistance in the prior art are solved, and efficient thermal conductivity and bond self-repairing effects are achieved.
Patent Information
- Application Number
- CN202311423477.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The existing epoxy thermal adhesives are insufficient in high-power LED heat dissipation components, have high thermal resistance and poor permeability, and the traditional solder paste fixing method increases cost and pollution.
The epoxy thermal adhesive with high thermal conductivity and low thermal resistance is adopted, including low viscosity epoxy resin, phase change epoxy resin and modified low melting point metal powder. The thermal conductivity path is optimized through brazing, the thermal conductivity and bonding strength are improved, and a thermal repair self-healing curing agent is added to achieve self-healing of fracture.
It achieves high thermal conductivity, low thermal resistance and good permeability, can effectively fill narrow slots, has self-healing function for fracture, and ensures bond reliability for long-term use.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of epoxy thermal conductive adhesives, and in particular to the field of a high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive used in high-power LED heat dissipation components and a preparation method thereof. Background Art
[0002] The power of high-power LED square lights, stage lights and photography lights is 500W-2000W or even higher, and the working heat is large. In order to increase the service life of high-power chips, the heat is exported from the aluminum substrate to the aluminum heat sink shell using a high thermal conductivity heat pipe. When the heat pipe is connected to the aluminum heat sink, a hole is first opened on one side of the aluminum heat sink with a hole depth of 2-20mm. The heat pipe is inserted into the hole of the aluminum heat sink, and the gap between the heat pipe and the inner wall of the aluminum heat sink hole is less than 0.1mm. In the traditional process, after the heat pipe is inserted into the hole of the aluminum heat sink, it is fixed with solder paste. The problem is that low-temperature tin series solders such as tin-bismuth, tin-silver-copper, etc. are difficult to wet on the aluminum surface after melting, and nickel needs to be electroplated on the aluminum surface in advance. At the same time, the opening of the aluminum heat sink will also be plated with nickel. Apply solder paste to the end of the heat pipe that needs to be connected to the radiator, insert it into the nickel-plated hole of the aluminum radiator, put it into the reflow oven and heat it to 150-270℃. The solder paste melts, and after cooling, connect the heat pipe and the aluminum radiator. Next, clean the residual additives of the solder paste. Electroplating and cleaning of solder paste residues increase costs, work hours and cause pollution. Epoxy thermal conductive adhesive has the characteristics of high bonding strength and adjustable thermal conductivity. The gap between the heat pipe and the inner wall of the aluminum radiator hole groove is less than 0.1mm, requiring the epoxy thermal conductive adhesive to have low viscosity, high permeability, low thermal resistance and high thermal conductivity. The thermal conductivity of traditional epoxy thermal potting glue is 2-3W / mK, and the viscosity is over 30000mPa.s, which has poor permeability and is not conducive to draining the air between the heat pipe and the hole slot. The thermal conductivity of air is 0.02W / mK, and the heat dissipation efficiency is low. The epoxy thermal potting glue of 2000-4500mPa.s meets the permeability requirements, but has high thermal resistance and low thermal conductivity, and does not meet the thermal conductivity requirements. The thermal conductive adhesive in the present invention has high thermal conductivity efficiency and low thermal resistance, can achieve narrow gap filling, has a self-repairing function during long-term use, and ensures bonding reliability. Summary of the invention
[0003] In view of the technical problems existing in the prior art, the present invention provides a high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive applied to a high-power LED heat dissipation component. The epoxy resin matrix in the epoxy thermal conductive adhesive includes a phase change epoxy resin to improve the thermal conductivity of the epoxy resin. The curing agent in the epoxy thermal conductive adhesive includes a heat-repairable self-healing curing agent, so that the epoxy adhesive has a self-repairing function when it is broken after curing. The epoxy thermal conductive adhesive includes a modified low-melting point metal powder to form a brazing between the modified metal thermal conductive powders, optimize the thermal conduction path, and improve the thermal conductivity and bonding strength. The specific composition of the epoxy thermal conductive adhesive is as follows:
[0004] Epoxy resin matrix 100 parts
[0005] Dispersant 1-2 parts
[0006] Adhesion promoter: 2-4 parts
[0007] Modified spherical nickel powder (D50 = 0.1-10um) 50-300 parts
[0008] Modified low melting point metal powder (D50 = 0.5-2um) 50-100 parts
[0009] Modified metal thermal conductive powder (D50 = 5-10um) 150-300 parts
[0010] Oxide thermal conductive powder (D50 = 0.2-2um) 50-150 parts
[0011] 1-3 parts of defoamer
[0012] Anti-settling agent 0.5-2 parts
[0013] Curing agent 15-100 parts
[0014] 3-5 parts of curing accelerator
[0015] Based on the above composition, a high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive used for high-power LED heat dissipation components, the epoxy resin matrix is composed of low viscosity epoxy resin, phase change epoxy resin liquid and epoxy reactive diluent, and the relative composition of each component is: the low viscosity epoxy resin accounts for 40-60% of the epoxy resin matrix, the phase change epoxy resin liquid accounts for 10-30% of the epoxy resin matrix, and the remainder of the epoxy resin matrix is epoxy reactive diluent. Based on the above epoxy resin matrix composition, the low viscosity epoxy resin is a liquid epoxy resin with a viscosity lower than 5000cs, specifically a bisphenol A epoxy resin with a viscosity lower than 5000mPa.s, a bisphenol F epoxy resin with a viscosity lower than 5000mPa.s, tetrahydrophthalic acid glycidyl ester, hexahydrophthalic acid glycidyl ester, 1,3-cyclohexanedimethylamine glycidyl amine, 4-(diglycidylamino)phenyl glycidyl ether with a viscosity lower than 5000mPa.s, 4,4-diaminodiphenylmethane tetraglycidyl amine with a viscosity lower than 5000mPa.s, resorcinol glycidyl ether, 4,5-epoxyhexane-1,2-dicarboxylic acid diglycidyl ester, and one or more combinations thereof. The low viscosity epoxy resin has the characteristics of high curing strength, strong bonding force, low viscosity and strong permeability, and can achieve a high addition amount of thermal conductive powder. Changchun Chemical's low-viscosity bisphenol A epoxy resin BEH-3250S has a viscosity of 800-1800mPa.s, bisphenol F epoxy resins include Hexion's EPON862, Changchun Chemical's low-viscosity bisphenol F epoxy resin BFE-235 has a viscosity of 2500-4500mPa.s, BFE-283 has a viscosity of 700-1000mPa.s, BEF3230S has a viscosity of 400-1000mPa.s. Shanghai Huayi Resin Factory's 4-(diglycidylamino)phenyl glycidyl ether ADBEST@R AFG90H has a viscosity of 900mPa.s, and a viscosity of 1500-4000mPa.s, Tiantai Chemical's hexahydrophthalic acid glycidyl ester TT284, tetrahydrophthalic acid glycidyl ester, TT490 1,3-cyclohexanedimethylamine's glycidylamine.
[0016] Based on the above epoxy resin matrix composition, the phase change epoxy resin liquid is composed of epoxy resin E44 (the reaction product of bisphenol A and epichlorohydrin, the epoxy value is 0.44), diphenylmethane-4,4' diisocyanate (4,4'-MDI) and high molecular weight polyethylene glycol reaction product phase change epoxy resin and epoxy reactive diluent, and the high molecular weight polyethylene glycol further has a molecular weight of 1500 melting point 43-46 ° C, a molecular weight of 4000 melting point 53-54 ° C and a molecular weight of 8000 melting point 60-63 ° C. Three molecular weight polyethylene glycols are mixed in a mass ratio of 2:3:5. When the high molecular weight polyethylene glycol reaches the melting temperature, it changes from solid to liquid. This process absorbs a lot of heat, and the phase change enthalpy value is higher than 200 J / g. First, the terminal hydroxyl group of the high molecular weight polyethylene glycol reacts with the isocyanate group of 4,4'-MDI to generate terminal isocyanate polyethylene glycol. The isocyanate group in the terminal isocyanate polyethylene glycol reacts with the secondary hydroxyl group in the epoxy resin E44 to graft the high molecular weight polyethylene glycol into the epoxy resin network. The thermal conductivity of epoxy resin cured product is 0.18-0.2W / mK. The high molecular weight polyethylene glycol with high phase change endothermic enthalpy value in the grafted part will absorb a lot of heat when the working temperature of the high-power LED lamp rises to its phase change melting temperature (45-62℃), which is equivalent to increasing the thermal conductivity of the epoxy resin. Based on the above epoxy resin matrix composition, the preparation process of the phase change epoxy resin liquid is as follows: epoxy resin E44, high molecular weight polyethylene glycol mixture (polyethylene glycol with molecular weight of 1500 and melting point of 43-46°C, molecular weight of 4000 and melting point of 53-54°C and molecular weight of 8000 and melting point of 60-63°C are mixed in a mass ratio of 2:3:5) are respectively vacuumed at 100-120°C for 1 hour to remove moisture, and then cooled to room temperature, a certain amount of dehydrated high molecular weight polyethylene glycol mixture is first added to the reactor, and then the temperature is raised to 80°C, and a measured amount of 4,4'-MDI ( The reaction was carried out for 2 hours under nitrogen atmosphere (in molar ratio, isocyanate group / hydroxyl group = 2:1) to obtain isocyanate-terminated polyethylene glycol, and then epoxy resin E44 from which moisture was removed was added (in molar ratio, isocyanate group / hydroxyl group of isocyanate-terminated polyethylene glycol = 1:1), and the reaction was continued for 2 hours under nitrogen atmosphere at 80°C to obtain phase-change epoxy resin, and epoxy reactive diluent was added to vacuum and stirred for 1 hour, and the amount of epoxy reactive diluent was 5-10% of the total amount of epoxy resin E44, diphenylmethane-4,4' diisocyanate (4,4'-MDI), and high molecular weight polyethylene glycol. The epoxy reactive diluent plays the role of adjusting viscosity, which is convenient for discharging and feeding of phase-change epoxy resin liquid.
[0017]
[0018] The epoxy active diluent in the above epoxy resin matrix and phase change epoxy resin liquid is one or a combination of C12-14 glycidyl ether, polypropylene glycol diglycidyl ether, ethylene glycol diglycidyl ether, propoxyglycerol triglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, neopentyl glycol diglycidyl ether and N,N-di(glycidyl)aniline, and cardanol epoxy diluent.
[0019] Based on the above composition of a high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive used in high-power LED heat dissipation components, the curing agent includes a thermal repair self-healing curing agent, a molecular chain extender and a main curing agent. The thermal repair self-healing curing agent is a reaction product of liquid polyethylene glycol, diphenylmethane-4,4' diisocyanate and a diphenol compound in a certain proportion. When the epoxy adhesive breaks, the thermal repair self-healing curing agent can decompose at above 120°C to produce terminal isocyanate prepolymers and diphenol compounds. The terminal isocyanate group can react with the hydroxyl group produced by the curing of the epoxy resin, and the diphenol compound can react with the unreacted epoxy group to play a role in repairing cracks; the liquid polyethylene glycol is one or two of PEG200 and PEG400, and the diphenol compound is diphenol. A mixture of one or more of phenol A, hydroquinone, and biphenol; the thermally repairable self-healing curing agent is prepared as follows: liquid polyethylene glycol is vacuumed at 120°C to remove moisture for 1 hour, cooled to room temperature, liquid polyethylene glycol is added to a stirring kettle and heated to 75-80°C, a measured amount of 4,4'-MDI (hydroxyl group and isocyanate group molar ratio: 1:2) is added and reacted for 2 hours to obtain terminal isocyanate polyethylene glycol, and then a measured amount of a diphenol compound (phenolic hydroxyl group: terminal isocyanate polyethylene glycol isocyanate group = 1:1) is added and reacted for 2 hours and cooled to room temperature to obtain a thermally repairable self-healing curing agent.
[0020]
[0021] Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used for high-power LED heat dissipation components, a molecular chain extender in the curing agent is a mixture of one or more of n-hexylamine, N,N-dimethyl-1,3-propanediamine, N,N-dimethyl-1,6-hexanediamine, N,N-diethyl-1,6-hexanediamine, adipic acid, isoadipic acid, difunctional polyaspartic acid resin containing secondary amine, 4,4'-bis-sec-butylaminodiphenylmethane MDBA, bisphenol A, bisphenol F, and hydrogenated bisphenol A.
[0022] Based on the above composition of high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive used in high-power LED heat dissipation components, the main curing agent in the curing agent is one or more combinations of polyetheramine curing agent, alicyclic amine curing agent, phenolic amine, hindered amine, methyltetrahydrophthalic anhydride, and methylhexahydrophthalic anhydride. The polyetheramine is a mixture of one or more amino-terminated polyethylene glycol or polypropylene glycol containing 2-3 primary amino groups in the molecule and a molecular weight of 230, 400, 1000 and 2000; the alicyclic amine curing agent is a mixture of one or more of isophorone diamine IPDA, 1,3-cyclohexanedimethylamine BAC, methylcyclopentane diamine TAC, 4,4'-diaminobis 3-methylcyclohexylmethane, and 4,4'-sub-dicyclohexylamine; the phenolic amine curing agent is a mixture of one or more of the reactants of aromatic amine, formaldehyde or polyformaldehyde and phenolic compounds; the hindered amine is a mixture of one or more of diethyltoluenediamine and 2-amino-2-methyl-1-propanol.
[0023] Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used for high-power LED heat dissipation components, the thermal repair self-healing curing agent in the curing agent accounts for 10%-20% of the curing agent, the molecular chain extender accounts for 1-10% of the curing agent, and the balance of the curing agent is the main curing agent.
[0024] Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition applied to high-power LED heat dissipation components, the dispersant includes one or more combinations of BYK163, BYK P104, BYKP105 and BYK-W9010.
[0025] Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used in high-power LED heat dissipation components, the adhesion promoter includes one or two combinations of silane coupling agent KH560 and epoxysiloxane oligomers, such as one or two combinations of um-BX60, um-BX70BYK-410, and BYK7410ET of Wuhan Enric Materials Co., Ltd.
[0026] Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used for high-power LED heat dissipation components, the curing accelerator includes tertiary amine accelerator 2,4,6-tris (dimethylaminomethyl) phenol DMP30, 2-methylimidazole, 2-ethyl 4-methylimidazole, tetraimidazole 2E4Mz-CN, substituted urea accelerator, microcapsule accelerator, diazabicyclo 1,8-diazabicyclo undec-7-ene hydrochloride, or one or more combinations thereof.
[0027] Based on the above-mentioned high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive used for high-power LED heat dissipation components, the modified spherical nickel powder (D50=0.1-10um), modified low melting point metal powder (D50=0.5-2um), and modified metal thermal conductive powder (D50=5-10um) are formed by spherical nickel powder (D50=0.1-10um), low melting point metal powder (D50=0.5-2um) and metal thermal conductive powder (D50=5-10um) coated with an organic modifier.
[0028] Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used in high-power LED heat dissipation components, the modified metal thermal conductive powder is one or a combination of modified spherical aluminum powder and modified spherical copper powder, and the median particle size D50 of the modified metal thermal conductive powder ranges from 5 to 20 um, and further D50 = 5 to 10 um.
[0029] Based on the above composition of a high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive used in high-power LED heat dissipation components, the low melting point metal powder is one or a combination of indium tin alloy powder In52Sn48 (melting point 120°C), indium bismuth tin alloy powder In68Bi15.72Sn16.3 (melting point 81°C), indium bismuth alloy powder In66Bi34 (melting point 72°C), and tin bismuth alloy powder Sn42Bi58 (melting point 139°C). The above alloy powders can be purchased directly or the metals in the alloy can be purchased and melted and mixed according to the mass ratio. The low melting point metal powder is made by an aerosol method. The low melting point metal is first melted, and then a high-speed high-pressure nitrogen gas flow is used to break the liquid metal flow into small droplets and solidify it into powder, and then the required D50=0.5-2um micropowder is collected by cyclone classification and sieve. In order to reduce costs and improve utilization, low-melting-point metal powders below 5 microns can also be obtained by wet sanding after adding dispersants, antioxidants, and solvents to low-melting-point metal powders above 5 microns. Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used for high-power LED heat dissipation components, the modified spherical nickel powder, modified low-melting-point metal powder, and modified metal thermal conductive powder are formed by coating spherical nickel powder, low-melting-point metal powder, and metal thermal conductive powder with organic modifiers, and the organic modifier further comprises PEG modifier, adipic acid, and isoadipic acid. The PEG modifier is further formed by mixing high molecular weight polyethylene glycol (PEG) and methyltetrahydrophthalic anhydride or methylhexahydrophthalic anhydride and reacting at high temperature. The terminal hydroxyl group of the high molecular weight polyethylene glycol reacts with the anhydride group in methyltetrahydrophthalic anhydride or methylhexahydrophthalic anhydride to produce a terminal carboxyl group, which can be adsorbed on the surface of spherical nickel powder, low-melting-point metal powder, and metal thermal conductive powder, and can also react with epoxy resin to solidify. Furthermore, the molecular weight range of the high molecular weight polyethylene glycol is 1500-8000, and the melting point range is 43-63°C. Polyethylene glycol with a molecular weight of 1500 and a melting point of 43-46°C, a molecular weight of 4000 and a melting point of 53-54°C, and a molecular weight of 8000 and a melting point of 60-63°C are selected and mixed in a mass ratio of 2:3:5; further, the synthesis method of the PEG modifier is as follows: the high molecular weight polyethylene glycol is reacted with methyltetrahydrophthalic anhydride or methylhexahydrophthalic anhydride, and the mixture is mixed and stirred at 100°C for 2 hours at a hydroxyl group / acid anhydride group molar ratio of 1:1 to obtain the PEG modifier.
[0030]
[0031] Based on the above-mentioned high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used in high-power LED heat dissipation components, the preparation process of the modified spherical nickel powder, modified low melting point metal powder, modified metal thermal conductive powder, and modified metal thermal conductive powder is as follows: PEG modifier, adipic acid, and isoadipic acid (according to a mass ratio of 5:3:2) are dissolved in anhydrous alcohol to prepare a 5% organic acid solution, the mass ratio of the modifier (the total mass of the PEG modifier, adipic acid, and isoadipic acid) to the metal powder is 2-3%, and the metal thermal conductive powder is added to the organic acid solution, mixed and stirred at 50°C for 5 hours, then filtered, and then vacuum dried in a 50°C vacuum drying oven.
[0032] Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used in high-power LED heat dissipation components, the oxide thermal conductive powder is single crystal aluminum oxide powder (D50=0.2-2um) or zinc oxide powder (D50=0.2-2um).
[0033] Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used for high-power LED heat dissipation components, the defoaming agent is a mixture of one or more of silicone defoaming agent BYK-066N, polymer defoaming agent BYKA535, polymer defoaming agent BYK1765, polymer defoaming agent BYK1788, polymer defoaming agent BYK054, and silicone / polymer defoaming agent BYKA530.
[0034] Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used in high-power LED heat dissipation components, the anti-settling agent is a mixture of one or more of organic modified bentonite, polyurea thixotropic agent, low molecular weight polyamide, hydrogenated castor oil and fumed silica.
[0035] Based on a high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used in high-power LED heat dissipation components, the preparation method is as follows: melt the low melting point metal, then use a high-speed high-pressure nitrogen gas flow to break the liquid metal into small droplets and solidify it into powder, and then collect the required D50 = 0.5-2um micropowder through cyclone classification, and control the maximum particle size to be no more than 30um through a 500-mesh sieve. Spherical nickel powder (D50 = 0.1-10um), low melting point metal powder (D50 = 0.5-2um), and metal thermal conductive powder (D50 = 5-10um) are passed through a 500-mesh sieve to control the maximum particle size to be no more than 30um. PEG modifier, adipic acid and isoadipic acid (in a mass ratio of 5:3:2) are dissolved in anhydrous alcohol to prepare a 5% organic acid solution, in which the mass of the organic modifier (the total mass of the PEG modifier, adipic acid and isoadipic acid) accounts for 2-3% of the mass of the metal powder to be modified. Various metal thermal conductive powders are added to the organic acid solution, mixed and stirred at 50°C for 2 hours, then washed and filtered with alcohol, and then vacuum dried in a vacuum drying oven at 50°C. The epoxy resin matrix, dispersant, adhesion promoter, modified spherical nickel powder (D50 = 0.1-10um), modified low melting point metal powder (D50 = 0.5-2um), oxide thermal conductive powder (D50 = 0.2-2um) and modified metal thermal conductive powder (D50 = 5-10um) are added to a double planetary mixer and vacuumed and stirred at a speed of 30-70 rpm for 1 hour, and then a defoamer and an anti-settling agent are added and vacuumed and stirred at a speed of 30 rpm for 0.5 hour to obtain epoxy thermal conductive adhesive component A. Then, a curing agent and a curing promoter are added according to the metered amount and vacuumed and stirred at a speed of 30 rpm for 0.5 hour to obtain epoxy thermal conductive adhesive component B.
[0036] Beneficial Effects
[0037] The thermal conductivity of air is 0.02W / mK. After the heat pipe is inserted into the slot of the aluminum radiator, the single-side gap between the heat pipe and the inner wall of the slot is an air layer of 0.02-0.1mm. The epoxy thermal conductive adhesive in the present invention has low viscosity and can fully discharge the air between the heat pipe and the inner wall of the slot, and the air in the micropores; the nickel powder in the epoxy thermal conductive adhesive is magnetic. A magnetic field is applied to the bottom of the heat pipe and the slot by a magnet or an electromagnet. The spherical nickel powder in the thermal conductive adhesive pushes the epoxy thermal conductive adhesive to flow forward under the gravitational force of the magnetic field, and fully fills and wets the gap between the heat pipe and the inner wall at the bottom of the aluminum radiator opening. The organic acid modifier on the surface of the modified spherical nickel powder, the modified metal thermal conductive powder and the modified low-melting point metal powder removes the metal oxide layer. The low-melting point metal is more likely to melt and liquefy into liquid metal before the epoxy resin is cured. The cohesive force inside the liquid metal is greater than the interaction force between the epoxy resin curing system and the adjacent low-melting point alloys. The liquid metals formed after the melting of the low-melting point alloys shrink and connect together. At the same time, the heat pipe will partially expand in volume at a high temperature above 120°C. Limited by the hole size of the aluminum radiator, copper metal thermal conductive powder (D50=5-10um) or nickel metal thermal conductive powder (D50=5-10um) with a larger particle size is extruded. After the surfaces of the copper metal micropowder and the nickel metal micropowder are activated by organic acid treatment, the epoxy resin cured product mixture is squeezed out under the action of extrusion and gravity, and is more susceptible to wetting and bonding by the liquid metal. After cooling, the large-particle spherical nickel powder and the large-particle spherical copper powder are equivalent to being micro-brazed, which enhances the strength of the thermal conductive adhesive, forms a metal thermal conductive channel, and improves thermal conductivity. The modified spherical nickel powder, modified low melting point metal powder, oxide thermal conductive powder and modified metal thermal conductive powder are matched with large and small particle sizes to control large particles, and the configured thermal conductive adhesive has low thermal resistance. At the same time, the high molecular weight polyethylene glycol in the phase change epoxy resin and the high molecular weight PEG modifier on the surface of the modified spherical nickel powder, modified low melting point metal powder and modified metal thermal conductive powder undergo phase change and absorb heat when the thermal conductive adhesive is heated, thereby improving the thermal conductivity of the epoxy curing system. At the same time, the high molecular weight PEG modifier has low viscosity after melting, which helps to wet the inner wall of the heat pipe and the hole of the aluminum radiator, thereby improving the heat dissipation efficiency. At the same time, the flexible chain of the high molecular weight PEG also has the function of toughening the epoxy curing system and improving the bonding strength. If the epoxy thermal conductive adhesive breaks or cracks during its later use and the temperature is raised to above 150°C, the thermal repair self-healing curing agent in the adhesive will decompose to produce isocyanate-terminated polyethylene glycol prepolymer and diphenol. The isocyanate-terminated can react with the hydroxyl groups in the epoxy curing material, and the diphenol can react with the unreacted epoxy groups in the epoxy curing material to achieve self-repair, making the cracks disappear and ensuring long-term bonding reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The reaction synthesis route for phase change epoxy resin Figure 2 Synthesis reaction route of self-healing curing agent for thermal repair Figure 3 Synthesis route of PEG modifier Specific implementation cases
[0039] 1. Synthesis and preparation of PEG modifier:
[0040] 20 parts of polyethylene glycol PEG-1500 (Haian Petrochemical Plant, Jiangsu Province, molecular weight 1500, melting point 43-46°C), 30 parts of polyethylene glycol PEG-3000 (Haian Petrochemical Plant, Jiangsu Province, molecular weight 3000, melting point 53-54°C) and 50 parts of polyethylene glycol PEG-8000 (Haian Petrochemical Plant, Jiangsu Province, molecular weight 8000, melting point 60-63°C) were heated to above 62°C in a reactor to melt, and then 9.83 parts of methyltetrahydrophthalic anhydride (hydroxyl / acid anhydride molar ratio = 1:1) were added, mixed and stirred at 100°C for 2 hours, and then cooled to room temperature to obtain a PEG modifier.
[0041] 2. Synthesis and preparation of phase change epoxy resin liquid
[0042] Epoxy resin E44 and polyethylene glycol were vacuumed for 2 hours in a reactor at 100-120°C to remove moisture, and then cooled for use. 20 parts of polyethylene glycol PEG-1500 (Jiangsu Hai'an Petrochemical Plant, molecular weight 1500, melting point 43-46°C), 30 parts of polyethylene glycol PEG-3000 (Jiangsu Hai'an Petrochemical Plant, molecular weight 3000, melting point 53-54°C) and 50 parts of polyethylene glycol PEG-8000 (Jiangsu Hai'an Petrochemical Plant, molecular weight 8000, melting point 60-63°C) were added to the reactor, slowly heated to 80°C, 14.81 parts of 4,4'-MDI were gradually added in batches, and reacted under a nitrogen atmosphere. 2 hours to obtain terminal isocyanate polyethylene glycol, and then 67.23 parts of epoxy resin E44 (molar ratio: isocyanate group of terminal isocyanate polyethylene glycol / hydroxyl group = 1:1, the hydroxyl value of E44 is 0.088 mol / 100 g according to theoretical calculation) from which moisture was removed was added, and the reaction was continued for 2 hours in a nitrogen atmosphere at 80°C, and 15 parts of epoxy reactive diluent 1,4-cyclohexanedimethanol diglycidyl ether XY630 (Anhui Xinyuan Technology Co., Ltd.) were added, and the phase change epoxy resin liquid was obtained by vacuum stirring for 1 hour.
[0043] 3. Synthesis and preparation of self-healing curing agent for thermal repair
[0044] PEG400 was vacuumed at 120°C to remove moisture for 1 hour, cooled to room temperature, 100 parts of PEG-400 were added to a stirred kettle, the temperature was raised to 75-80°C, 125.06g of 4,4'-MDI (hydroxyl and isocyanate group molar ratio: 1:2) was added to react in a nitrogen atmosphere for 2 hours to obtain isocyanate-terminated polyethylene glycol, and then 57.07g of bisphenol A (phenolic hydroxyl: isocyanate-terminated polyethylene glycol isocyanate group = 1:1) was added to react for 2 hours and cooled to room temperature to obtain a thermally repaired self-healing curing agent. Preparation of a high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive for high-power LED heat dissipation components.
[0045] Example 1
[0046] The low melting point indium bismuth tin alloy powder In68Bi15.72Sn16.3 was heated to above 81°C to melt, and then the liquid metal was broken into small droplets and solidified into powder by high-speed high-pressure nitrogen gas flow, and then the required D50 = 1.5um micropowder was collected by airflow classification and sieving, and the maximum particle size was controlled to be no more than 30um through a 500-mesh sieve. Spherical nickel powder with D50 = 0.5um (Changsha Tianjiu Metal), alumina powder with D50 = 0.6um (AP06 Tianjin Zexi New Materials Co., Ltd.), spherical nickel powder with D50 = 5um (Forsman Beijing Technology Co., Ltd.), and spherical copper powder with D50 = 10um (Changsha Tianjiu Metal) were sieved through a 500-mesh sieve to control the maximum particle size to be no more than 30um. Dissolve 5 parts of PEG modifier, 3 parts of adipic acid, and 2 parts of isoadipic acid in 190 parts of alcohol to prepare a 5% organic acid modifier solution, add 333 parts of various metal powders to be modified, mix and stir at 50°C for 2 hours, wash and filter with alcohol, and vacuum dry in a 50°C vacuum drying oven. 50 parts of low-viscosity epoxy compound ADBEST@RAFG90H adhesive, 30 parts of phase-change epoxy resin liquid, 20 parts of cyclohexanedimethanol diglycidyl ether XY630 (Anhui Xinyuan Technology Co., Ltd.), 2 parts of BYK-P104S, 2.5 parts of adhesion promoter UM-BX70 (Wuhan Enric Materials Co., Ltd.), 50 parts of spherical nickel powder with D50=0.5um (Changsha Tianjiu Metal), 50 parts of alumina powder with D50=0.6um, 50 parts of low-melting-point In68Bi15.72Sn16.3 powder with D50=1.5um, 200 parts of spherical nickel powder with D50=5um, and 300 parts of spherical copper powder with D50=10um were stirred in a double planetary mixer under vacuum at a stirring speed of 30-70 rpm for 1 hour, and then defoamer BYKA530 was added. 1 part, anti-settling agent BYK-4010 1 part, vacuum stirring, stirring speed 30 rpm, stirring time 0.5 hour, to obtain epoxy thermal conductive adhesive component A. Then, according to the metering, add 10 parts of thermal repair self-healing curing agent, 2 parts of chain extender N,N-diethyl-1,6-hexanediamine, 73 parts of BASF polyetheramine D400, and 2 parts of curing accelerator DMP30 into a double planetary mixer, vacuum stirring, stirring speed 30 rpm, stirring time 0.5 hour, to obtain component B. When using components A and B, first mix and stir to vacuum degas, then dispense glue, apply a magnetic field at the bottom of the heat pipe inserted into the aluminum radiator opening, guide the thermal conductive adhesive to fully penetrate the gap between the heat pipe and the radiator opening, drive away the air in the gap, and then cure, the curing process is 85℃ / 0.5 hour, and then cure at 120℃ for 2 hours.
[0047] Example 2
[0048] The low melting point indium tin alloy powder In52Sn48 was heated to above 120°C to melt, and then the liquid metal was broken into small droplets and solidified into powder by high-speed high-pressure nitrogen gas flow, and then the required D50 = 1.0um micropowder was collected by airflow classification, and the maximum particle size was controlled to be no more than 30um through a 500-mesh sieve. Zinc oxide powder with D50 = 0.5um (Dalian Jinshi Zinc Oxide Co., Ltd.), spherical nickel powder with D50 = 5um (Forsman Beijing Technology Co., Ltd.), and spherical aluminum powder with D50 = 8um (Henan Yuanyang Aluminum Co., Ltd.) were passed through a 500-mesh sieve to control the maximum particle size to be no more than 30um. 5 parts of PEG modifier, 3 parts of adipic acid, and 2 parts of isoadipic acid were dissolved in 190 parts of alcohol to prepare a 5% organic acid modifier solution, and 333 parts of various metal powders to be modified were added, mixed and stirred at 50°C for 2 hours, and then washed and filtered with alcohol, and then vacuum dried in a 50°C vacuum drying oven. 50 parts of bisphenol F epoxy resin BFE-283 (Changchun Chemical, viscosity 700-1000mPa.s), 20 parts of phase change epoxy resin liquid, 30 parts of propoxyglycerol triglycidyl ether XY670 (Anhui Xinyuan Technology Co., Ltd.), 2 parts of BYK-P104S, 2.5 parts of adhesion promoter UM-BX70 (Wuhan Enric Materials Co., Ltd.), 50 parts of zinc oxide powder with D50=0.5um, 100 parts of low melting point In52Sn48 powder with D50=1um, 300 parts of spherical nickel powder with D50=5um, and 150 parts of spherical aluminum powder with D50=8um were vacuum stirred in a double planetary mixer at a stirring speed of 30-70 rpm for 1 hour, and then 1 part of defoamer BYKA530 and anti-settling agent BYK-4010 were added. 1 part of the mixture was stirred in vacuum at a speed of 30 rpm for 0.5 hours to obtain component A of epoxy thermal conductive adhesive. Then, 20 parts of curing agent 1,3-cyclohexanedimethylamine, 4 parts of 4,4'-bis-sec-butylaminodiphenylmethane, and 2 parts of curing accelerator 2-ethyl-4-methylimidazole were added into a double planetary mixer according to the measurement, and vacuum stirred at a speed of 30 rpm for 0.5 hours to obtain component B. When using components A and B, they were first mixed and stirred to vacuum degas, and then glue was dispensed. A magnetic field was applied to the bottom of the opening of the heat pipe inserted into the aluminum radiator to guide the thermal conductive adhesive to fully penetrate the gap between the heat pipe and the radiator opening, and the temperature was raised to 120°C for 10 minutes, and then cured at 130°C for 2 hours.
[0049] Example 3
[0050] The low melting point tin-bismuth alloy powder Sn42Bi58 is heated to above 139°C to melt, and then the liquid metal is broken into small droplets and solidified into powder by high-speed high-pressure nitrogen gas flow, and then the required D50 = 0.7um micropowder is collected by airflow classification, and the maximum particle size is controlled to be no more than 30um through a 500-mesh sieve. The alumina powder AP06 with D50 = 0.6um (Tianjin Zexi New Materials Co., Ltd.), spherical nickel powder with D50 = 5um (Forsman Beijing Technology Co., Ltd.), and spherical copper powder with D50 = 10um (Changsha Tianjiu Metal) are passed through a 500-mesh sieve to control the maximum particle size to be no more than 30um. 5 parts of PEG modifier, 5 parts of adipic acid, and 2 parts of isoadipic acid are dissolved in 190 parts of alcohol to prepare a 5% organic acid modifier solution, and 333 parts of various metal powders to be modified are added, mixed and stirred at 50°C for 2 hours, then washed and filtered with alcohol, and then vacuum dried in a 50°C vacuum drying oven. 60 parts of hexahydrophthalic acid glycidyl ester TT284 (Tiantai Chemical), 20 parts of phase change epoxy resin liquid, 20 parts of ethylene glycol diglycidyl ether ERISYS EGDGE, 2 parts of BYK-P104S and 2.5 parts of adhesion promoter UM-BX60 (Wuhan Enric Materials Co., Ltd.), 50 parts of alumina powder AP06, 100 parts of low melting point Sn42Bi58 powder with D50=0.7um, 300 parts of spherical nickel powder with D50=5um, and 300 parts of spherical copper powder with D50=10um were vacuum stirred in a double planetary mixing mixer at a stirring speed of 30-70 rpm for 1 hour, and then a defoamer and an anti-settling agent were added and vacuum stirred at a stirring speed of 30 rpm for 0.5 hour to obtain component A of epoxy thermal conductive adhesive. Then, 85 parts of curing agent methyltetrahydrophthalic anhydride, 8 parts of isoadipic acid, and 2 parts of curing accelerator 2-ethyl-4-methylimidazole were added into a double planetary mixer according to the measurement, and vacuum-stirred at a speed of 30 rpm for 0.5 hours to obtain component B. When using components A and B, they were first mixed and stirred to vacuum-degassing, and then glue was dispensed. A magnetic field was applied to the bottom of the opening of the heat pipe inserted into the aluminum radiator to guide the thermal conductive adhesive to fully penetrate the gap between the heat pipe and the radiator opening, and then cured. The curing process was 140℃ / 10 minutes, and then cured at 150℃ for 2 hours.
[0051] Comparative Example
[0052] 80 parts of low-viscosity bisphenol F epoxy resin BFE-170, 20 parts of ethylene glycol diglycidyl ether ERISYS EGDGE, 2 parts of BYK-P104S, 2.5 parts of adhesion promoter UM-BX60, 300 parts of spherical aluminum powder with D50=20um (Henan Yuanyang Aluminum Co., Ltd.), and 150 parts of alumina powder with D50=5um were added to a double planetary mixer and vacuumed and stirred at a speed of 30-70 rpm for 1 hour. Then, 1 part of defoamer BYKA530 and 1 part of anti-settling agent BYK-4010 were added and vacuumed and stirred at a speed of 30 rpm for 0.5 hour to obtain component A of epoxy thermal conductive adhesive. Then, add 1 part of curing agent isophorone diamine IPDA and 2 parts of curing accelerator DMP30 into a double planetary mixer according to the measurement, vacuum and stir at a speed of 30 rpm for 0.5 hours to obtain component B. When using components A and B, first mix and stir, vacuum and degas, then dispense glue, and then cure at 120°C for 2 hours.
[0053] The viscosity of the thermal conductive adhesive was tested before curing, and the thermal conductivity, thermal resistance, and shear strength of the aluminum sheet / heat pipe were tested after curing. The viscosity was tested using the ASTM D2196-2015 method, the thermal conductivity and thermal resistance were tested using the ASTM D5470 method, and the single lap shear strength of the aluminum sheet was tested using the GB T 7124-2008 method. The test results are shown in the following table.
[0054] project Example 1 Example 2 Example 3 Comparative Example Viscosity (mPa.s) 3800 4500 3500 3500 Thermal conductivity (W / mK) 6.5 5.3 8 2 Thermal resistance (℃ / W) 0.016 0.02 0.008 0.047 Aluminum Alloy 6061 Shear Strength 10.3 12.1 11.5 6.5
[0055] It can be seen from the test data that the thermal conductivity and bonding strength of Examples 1, 2, and 3 of the present invention are higher than those of the comparative examples, and the thermal resistance is lower than that of the comparative examples.
Claims
1. A high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive for high-power LED heat dissipation components, wherein the epoxy resin matrix in the epoxy thermal conductive adhesive comprises a phase change epoxy resin to improve the thermal conductivity of the epoxy resin, the curing agent in the epoxy thermal conductive adhesive comprises a heat-repairable self-healing curing agent, so that the epoxy adhesive has a self-repairing function when it is broken after curing, the epoxy thermal conductive adhesive comprises a modified low-melting point metal powder to form a brazing between the modified metal thermal conductive powders, optimize the thermal conduction path, and improve the thermal conductivity and bonding strength. The specific composition of the epoxy thermal conductive adhesive is as follows:
2. The high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive for high-power LED heat dissipation components according to claim 1, characterized in that The epoxy resin matrix is composed of low viscosity epoxy resin, phase change epoxy resin liquid and epoxy active diluent, wherein the low viscosity epoxy resin accounts for 40-60% of the epoxy resin matrix, the phase change epoxy resin liquid accounts for 10-30% of the epoxy resin matrix, and the remainder of the epoxy resin matrix is epoxy active diluent. Based on the above epoxy resin matrix composition, the low viscosity epoxy resin is a liquid epoxy resin with a viscosity of less than 5000cs, specifically a bisphenol A epoxy resin with a viscosity of less than 5000mPa.s, a bisphenol F epoxy resin with a viscosity of less than 5000mPa.s, tetrahydrophthalic acid glycidyl ester, hexahydrophthalic acid glycidyl ester, 1,3-cyclohexanedimethylamine glycidyl amine, 4-(diglycidylamino)phenyl glycidyl ether with a viscosity of less than 5000mPa.s, 4,4-diaminodiphenylmethane tetraglycidylamine with a viscosity of less than 5000mPa.s, resorcinol glycidyl ether, 4,5-epoxyhexane-1,2-dicarboxylic acid diglycidyl ester, and one or more combinations thereof. Based on the above epoxy resin matrix composition, the phase-change epoxy resin liquid is composed of the phase-change epoxy resin and epoxy reactive diluent of the reaction product of epoxy resin E44 (bisphenol A and epichlorohydrin, epoxy value 0.44), diphenylmethane-4,4' diisocyanate (4,4'-MDI) and high molecular weight polyethylene glycol, and further the high molecular weight polyethylene glycol is a mixture of three molecular weight polyethylene glycols with a molecular weight of 1500 and a melting point of 43-46°C, a molecular weight of 4000 and a melting point of 53-54°C, and a molecular weight of 8000 and a melting point of 60-63°C in a mass ratio of 2:3:
5. The terminal hydroxyl group of the high molecular weight polyethylene glycol reacts with the isocyanate group of 4,4'-MDI to generate terminal isocyanate polyethylene glycol, and the isocyanate group in the terminal isocyanate polyethylene glycol reacts with the secondary hydroxyl group in the epoxy resin E44 to graft the high molecular weight polyethylene glycol to the epoxy resin network. The preparation process of the phase change epoxy resin liquid is as follows: epoxy resin E44 and a high molecular weight polyethylene glycol mixture (polyethylene glycols with a molecular weight of 1500 and a melting point of 43-46°C, a molecular weight of 4000 and a melting point of 53-54°C, and a molecular weight of 8000 and a melting point of 60-63°C are mixed in a mass ratio of 2:3:5) are respectively vacuumed at 100-120°C for 1 hour to remove moisture, and then cooled to room temperature, a certain amount of the dehydrated high molecular weight polyethylene glycol mixture is first added to the reactor, and then the temperature is raised to 80°C, and a measured amount of 4,4'-MDI (in molar ratio, The reaction mixture is carried out for 2 hours under a nitrogen atmosphere to obtain an isocyanate-terminated polyethylene glycol, and then the epoxy resin E44 from which moisture has been removed is added (in molar ratio, the isocyanate group / hydroxyl group of the isocyanate-terminated polyethylene glycol is 1:1), and the reaction is continued for 2 hours in a nitrogen atmosphere at 80° C. to obtain a phase-change epoxy resin, and an epoxy reactive diluent is added to vacuum-dry and stirred for 1 hour, wherein the amount of the epoxy reactive diluent is 5-10% of the total amount of the epoxy resin E44, diphenylmethane-4,4'-diisocyanate (4,4'-MDI), and the high molecular weight polyethylene glycol. The epoxy active diluent in the above epoxy resin matrix and phase change epoxy resin liquid is one or a combination of C12-14 glycidyl ether, polypropylene glycol diglycidyl ether, ethylene glycol diglycidyl ether, propoxyglycerol triglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, neopentyl glycol diglycidyl ether and N,N-di(glycidyl)aniline, and cardanol epoxy diluent.
3. According to claim 1, a high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive for high-power LED heat dissipation components, characterized in that The curing agent comprises a heat-repairable self-healing curing agent, a molecular chain extender and a main curing agent. The heat-repairable self-healing curing agent is a reaction product of liquid polyethylene glycol, diphenylmethane-4,4' diisocyanate and a diphenolic compound in a certain proportion. When the epoxy adhesive breaks, the heat-repairable self-healing curing agent can decompose at above 120°C to produce terminal isocyanate prepolymer and diphenolic compound. The terminal isocyanate group can react with the hydroxyl group produced by epoxy resin curing, and the diphenolic compound can react with the unreacted epoxy group to play a role in repairing cracks; the liquid polyethylene glycol is one or two of PEG200 and PEG400, and the diphenolic compound is diisocyanate. A mixture of one or more of phenol A, hydroquinone, and biphenol; the thermally repairable self-healing curing agent is prepared as follows: liquid polyethylene glycol is vacuumed at 120°C to remove moisture for 1 hour, cooled to room temperature, liquid polyethylene glycol is added to a stirring kettle and heated to 75-80°C, a measured amount of 4,4'-MDI (hydroxyl group and isocyanate group molar ratio: 1:2) is added and reacted for 2 hours to obtain terminal isocyanate polyethylene glycol, and then a measured amount of a diphenol compound (phenolic hydroxyl group: terminal isocyanate polyethylene glycol isocyanate group = 1:1) is added and reacted for 2 hours and cooled to room temperature to obtain a thermally repairable self-healing curing agent. Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used for high-power LED heat dissipation components, a molecular chain extender in the curing agent is a mixture of one or more of n-hexylamine, N,N-dimethyl-1,3-propanediamine, N,N-dimethyl-1,6-hexanediamine, N,N-diethyl-1,6-hexanediamine, adipic acid, isoadipic acid, difunctional polyaspartic acid resin containing secondary amine, 4,4'-bis-sec-butylaminodiphenylmethane MDBA, bisphenol A, bisphenol F, and hydrogenated bisphenol A. Based on the above composition of high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive used in high-power LED heat dissipation components, the main curing agent in the curing agent is one or more combinations of polyetheramine curing agent, alicyclic amine curing agent, phenolic amine, hindered amine, methyltetrahydrophthalic anhydride, and methylhexahydrophthalic anhydride. The polyetheramine is a mixture of one or more amino-terminated polyethylene glycol or polypropylene glycol containing 2-3 primary amino groups in the molecule and a molecular weight of 230, 400, 1000 and 2000; the alicyclic amine curing agent is a mixture of one or more of isophorone diamine IPDA, 1,3-cyclohexanedimethylamine BAC, methylcyclopentane diamine TAC, 4,4'-diaminobis 3-methylcyclohexylmethane, and 4,4'-sub-dicyclohexylamine; the phenolic amine curing agent is a mixture of one or more of the reactants of aromatic amine, formaldehyde or polyformaldehyde and phenolic compounds; the hindered amine is a mixture of one or more of diethyltoluenediamine and 2-amino-2-methyl-1-propanol. Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition used for high-power LED heat dissipation components, the thermal repair self-healing curing agent in the curing agent accounts for 10%-20% of the curing agent, the molecular chain extender accounts for 1-10% of the curing agent, and the remainder of the curing agent is the main curing agent.
4. A high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition for high-power LED heat dissipation components according to claim 1, characterized in that: The curing accelerator comprises tertiary amino accelerator 2,4,6-tris(dimethylaminomethyl)phenol DMP30, 2-methylimidazole, 2-ethyl 4-methylimidazole, tetraimidazole 2E4Mz-CN, substituted urea accelerator, microcapsule accelerator, diazabicyclo 1,8-diazabicyclo undec-7-ene hydrochloride, or one or more combinations thereof.
5. A high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition for high power LED heat dissipation components according to claim 1, characterized in that The dispersant includes one or more combinations of BYK163, BYK P104, BYKP105 and BYK-W9010; the adhesion promoter includes one or more combinations of silane coupling agent KH560 and epoxysiloxane oligomer; the defoamer is a mixture of one or more of silicone defoamer BYK-066N, polymer defoamer BYKA535, polymer defoamer BYK1765, polymer defoamer BYK1788, polymer defoamer BYK054 and silicone / polymer defoamer BYKA530; the anti-settling agent is a mixture of one or more of organic modified bentonite, polyurea thixotropic agent, low molecular weight polyamide, hydrogenated castor oil and fumed silica.
6. A high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition for high power LED heat dissipation components according to claim 1, characterized in that The modified spherical nickel powder (D50 = 0.1-10um), modified low melting point metal powder (D50 = 0.5-2um), and modified metal thermal conductive powder (D50 = 5-10um) are formed by coating spherical nickel powder (D50 = 0.1-10um), low melting point metal powder (D50 = 0.5-2um), and metal thermal conductive powder (D50 = 5-10um) with an organic modifier. The modified metal thermal conductive powder is a combination of one or two of modified spherical aluminum powder and modified spherical copper powder, and the median particle size D50 of the modified metal thermal conductive powder is in the range of 5-20um, and further D50 = 5-10um. The low melting point metal powder is one or a combination of indium tin alloy powder In52Sn48 (melting point 120°C), indium bismuth tin alloy powder In68Bi15.72Sn16.3 (melting point 81°C), indium bismuth alloy powder In66Bi34 (melting point 72°C), tin bismuth alloy powder Sn42Bi58 (melting point 139°C). The low melting point metal powder is made by aerosol method, firstly melting the low melting point metal, then breaking the liquid metal flow into small droplets with high-speed high-pressure nitrogen gas flow and solidifying it into powder, and then collecting the required D50=0.5-2um micro powder through cyclone classification and sieve. Further, the above-mentioned organic modifier includes PEG modification, adipic acid and isoadipic acid; further, the PEG modifier is formed by mixing high molecular weight polyethylene glycol (PEG) and methyltetrahydrophthalic anhydride or methylhexahydrophthalic anhydride and reacting at high temperature; further, the molecular weight range of the high molecular weight polyethylene glycol is 1500-8000, the melting point range is 43-63°C, and polyethylene glycol with a molecular weight of 1500 and a melting point of 43-46°C, a molecular weight of 4000 and a melting point of 53-54°C, and a molecular weight of 8000 and a melting point of 60-63°C are selected and mixed in a mass ratio of 2:3:5; further, the synthesis method of the PEG modifier is: high molecular weight polyethylene glycol reacts with methyltetrahydrophthalic anhydride or methylhexahydrophthalic anhydride, and the mixture is stirred and reacted at 100°C for 2 hours at a hydroxyl / acid anhydride group molar ratio of 1:1; based on the above one kind of high-power LED dispersion The invention discloses a high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition for thermal components. The modified spherical nickel powder, modified low melting point metal powder, modified metal thermal conductive powder and modified metal thermal conductive powder are prepared as follows: PEG agent, adipic acid and isoadipic acid (at a mass ratio of 5:3:2) are dissolved in anhydrous alcohol to prepare an organic acid solution with a concentration of 5%. The mass ratio of the modifier (the total mass of the PEG modifier, adipic acid and isoadipic acid) to the metal powder is 2-3%. The metal thermal conductive powder is added to the organic acid solution, mixed and stirred at 50°C for 5 hours, then filtered, and then vacuum dried in a vacuum drying oven at 50°C. Based on the above high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition applied to high-power LED heat dissipation components, the oxide thermal conductive powder is single crystal aluminum oxide powder (D50=0.2-2um) or zinc oxide powder (D50=0.2-2um).
7. A high thermal conductivity and low thermal resistance epoxy thermal conductive adhesive composition for high power LED heat dissipation components according to claim 1, characterized in that The preparation method is as follows: add epoxy resin matrix, dispersant, adhesion promoter, modified spherical nickel powder (D50 = 0.1-10um), modified low melting point metal powder (D50 = 0.5-2um), oxide thermal conductive powder (D50 = 0.2-2um) and modified metal thermal conductive powder (D50 = 5-10um) into a double planetary mixer and vacuum stir at a speed of 30-70 rpm for 1 hour, then add defoamer and anti-settling agent and vacuum stir at a speed of 30 rpm for 0.5 hour to obtain epoxy thermal conductive adhesive component A. Then add curing agent and curing accelerator into the double planetary mixer according to the metered amount and vacuum stir at a speed of 30 rpm for 0.5 hour to obtain epoxy thermal conductive adhesive component B.